Accountability and transparency in the German nonprofit sector: a paradox? - Anheier, Helmut K.; Haß, Rabea; Beller, Annelie (International review of public administration, 2014)
The article draws on exploratory research on the accountability and transparency of nonprofit organizations, using Germany as an example. In terms of accountability and transparency requirements, so frequently put forth and debated in the U.S., the UK, and other countries where nonprofits play major roles in social service delivery and public sector reform, the German case presents somewhat of a puzzle: while nonprofits account indeed for a sizable share of social service delivery, and while some of the world´s largest nonprofit conglomerates are in Germany, initial findings suggest an apparent “non-problem.” Both accountability and transparency requirements in the German nonprofit sector are rather low and largely part of formalistic reporting to tax authorities. What is more, there is a general paucity of available information on nonprofit organizations, combined with low levels of awareness among stakeholders as to potential accountability and transparency problems, and a lack of political will among nonprofit representatives and policymakers to change the status quo. In conclusion, we propose five theses to help explain this seeming paradox.